Applicability of Overreaction Hypothesis in the Bombay Stock Exchange - Gupta, Kartick (2005)
The goal of this dissertation is to examine applicability of overreaction hypothesis in Bombay Stock Exchange (BSE), which hasn’t been investigated in details before, and to thereby shed further light on competing explanations underlying these anomalies. First of all, the main emphasis was on to check whether a trader can book profit by employing this strategy. Purchasing past losers and short-selling past winners, our portfolio earned contrarian profit of 74.40% over market return in the post 36 months. Secondly, we found risk difference between Winner and Loser portfolio being an independent phenomenon. Jensen’s Performance Index didn’t indicate any statistically significant risk difference between Winner and Loser portfolio. Thirdly, size of the firm plays vital role in explaining overreaction hypothesis. When portfolios are matched of same market capitalization, contrarian profit has almost disappeared. On the contrary, contrarian profit jumped from 74.40% to 175.14% when Winner portfolio has highest market capitalization and smallest market capitalization for Loser portfolio. Finally, we found continuation of abnormal return after a sharp increase of +50% or more during any given month. Our results indicate cumulative abnormal return of 81.72% over market return after 36 months of event occurrence. Therefore, it seems that in medium term period, BSE follows momentum strategy.